Compressive Behaviour of Concrete by Using Bagasse Ash From Sugar Mill - Mahmud, Safayat; Islam, Md. Imamul; Ali, Rubieyat Bin; Islam, Md. Mofizul; Hasan, Md. Mahadi (Journal of Science and Technology, 2018)
The materials which are useless and unwanted is called waste product and this waste product is a burden and harmful to the environment. Sugarcane bagasse ash (SCBA) is one kind of waste which can be termed as the residue left over from burning sugar cane bagasse. The utilization of this waste may be very economical and can also solve the environmental problem. Silica and alumina are the main element of SCBA which is used as a pozzolanic material. This recycling procedure of SCBA reduces environmental pollution and this is also considered the cost-effective material. In this paper, SCBA replaces the cement as a weight of 5%, 10% and 15% which is considered. After completing the compressive strength test, the result shows that the compressive strength increases when 5% cement is replaced by sugarcane bagasse ash and this is the correct replacement of cement.